2008
DOI: 10.1002/ajmg.a.32161
|View full text |Cite
|
Sign up to set email alerts
|

The hair collar sign

Abstract: We report on two children with congenital scalp lesions which were surrounded by a ring of dark hair known as a hair collar. A review of previously reported patients with hair collars revealed that most of the scalp lesions were single and located at the vertex or parietal areas. They were most commonly composed of heterotopic neural tissue. We found a significant risk of associated skull defects, direct connections to the central nervous system (CNS), and brain and cerebrovascular anomalies in these patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It was not clear, however, due to the retrospective methodology of our study, whether a ‘hair collar’, i.e. overgrown hyperpigmented hair surrounding the central zone of alopecia, was present or not in many of our patients 18–23 …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It was not clear, however, due to the retrospective methodology of our study, whether a ‘hair collar’, i.e. overgrown hyperpigmented hair surrounding the central zone of alopecia, was present or not in many of our patients 18–23 …”
Section: Discussionmentioning
confidence: 82%
“…overgrown hyperpigmented hair surrounding the central zone of alopecia, was present or not in many of our patients. [18][19][20][21][22][23] The lesions were distributed on the skin overlying the neuraxis, most of them on the scalp, with a predilection for the parieto-occipital region. Scalp lesions were often outside the midline, perhaps overlying sutures of the cranium.…”
Section: Discussionmentioning
confidence: 99%
“…When an alopecic lesion surrounded by a hair collar is present, cranial imaging should be performed. This diagnostic measure is particularly relevant before planned biopsies or excisions [6].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from prior case reports suggest that the majority of cases of ACC occur as isolated cutaneous lesions, but nodules, midline lesions on the vertex, hair collar sign, and larger lesions have all been reported as warranting further investigation for underlying central nervous system (CNS) defects. Similar to previous reports, the results of our study confirmed the importance of clinical clues in suggesting scalp involvement . These clinical indicators include the hair collar sign, midline vertex location, size greater than 5 cm, vascular stains, and nodules.…”
Section: Introductionmentioning
confidence: 99%